2012
DOI: 10.1007/s10570-012-9711-7
|View full text |Cite
|
Sign up to set email alerts
|

Superabsorbent hydrogel nanocomposites based on starch-g-poly(sodium acrylate) matrix filled with cellulose nanowhiskers

Abstract: Superabsorbents hydrogel nanocomposites based on starch-g-poly(sodium acrylate) and cellulose nanowhiskers (CNWs) were synthesized. A set of experiments was performed to evaluate the influence of some factors such as NaAc/starch mass ratio, crosslinker, and nanowhiskers amount in the swelling capacity and swelling kinetics. Increasing the NaAc/starch mass ratio up to 7 leads to an increase in the water uptake at a maximum value, however, higher ratios decreased that value due to the increase of crosslinking po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 39 publications
4
67
0
1
Order By: Relevance
“…Illustration of the concept that a network of macroscopic cellulosic fibers in an absorbent product might tend to constrain the swelling of hydrogel particles. Left: Representation of dry condition; Right: Swollen condition As was noted earlier, when nanocellulose elements are incorporated into hydrogels, the observed result is generally a marked decrease in absorbency, often accompanied by an increase in the mechanical strength of the gel material (Dai et al 2009;Larsson et al 2010Larsson et al , 2011Spagnol et al 2012a). In an analogous manner to the mechanism just described to account for the restraining effects of fluff pulp fibers on SAP swelling, some authors have attributed the effects of nanocellulose on SAP absorbency to a "reinforcement" effect (Larsson et al 2011).…”
Section: Cellulosic Fibers and Hydrogel Swellingmentioning
confidence: 81%
See 4 more Smart Citations
“…Illustration of the concept that a network of macroscopic cellulosic fibers in an absorbent product might tend to constrain the swelling of hydrogel particles. Left: Representation of dry condition; Right: Swollen condition As was noted earlier, when nanocellulose elements are incorporated into hydrogels, the observed result is generally a marked decrease in absorbency, often accompanied by an increase in the mechanical strength of the gel material (Dai et al 2009;Larsson et al 2010Larsson et al , 2011Spagnol et al 2012a). In an analogous manner to the mechanism just described to account for the restraining effects of fluff pulp fibers on SAP swelling, some authors have attributed the effects of nanocellulose on SAP absorbency to a "reinforcement" effect (Larsson et al 2011).…”
Section: Cellulosic Fibers and Hydrogel Swellingmentioning
confidence: 81%
“…Spagnol et al (2012a) found that incorporation of cellulose nano-whiskers (i.e. long crystals) tended to increase the pore size of starchacrylic hydrogels.…”
Section: Maintaining Meso-pore Structurementioning
confidence: 98%
See 3 more Smart Citations